Preparation method and application of heat conduction material and maleic anhydride grafted graphene material

Through the grafting reaction of maleic anhydride and graphene, strongly polar groups are formed, which solves the problem of poor binding ability between graphene and plastic matrix, improves the toughness and thermal conductivity of thermal composite materials, simplifies the preparation process and Reduced costs and pollution.

CN119241783APending Publication Date: 2025-01-03XIAMEN KNANO GRAPHENE TECH CORP
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411485940.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The bonding ability of graphene microsheets to plastic matrix in traditional thermally conductive materials is poor, resulting in insufficient toughness, rough surface, and low fracture strength, which affects the performance and life of thermally conductive composite materials.

Method used

Maleic anhydride is mixed with graphene and reacted with peroxy initiator to form maleic anhydride grafted graphene material, enhancing the binding ability of graphene to the plastic matrix, and graft strong polar groups as connections through maleic anhydride Bridges to improve the toughness and thermal conductivity of thermal composite materials.

Benefits of technology

It significantly improves the toughness, surface smoothness and thermal conductivity of thermal composite materials, while simplifying the preparation process, reducing costs and pollution, and improving environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005098707010000081
    Figure BDA0005098707010000081
  • Figure BDA0005098707010000091
    Figure BDA0005098707010000091
  • Figure BDA0005098707010000101
    Figure BDA0005098707010000101
Patent Text Reader

Abstract

The invention relates to the technical field of carbon materials, in particular to a preparation method and application of a heat conduction material and a maleic anhydride grafted graphene material.The preparation method comprises the steps that maleic anhydride and graphene are evenly mixed, and a prefabricated mixture is obtained; uniformly mixing the prefabricated mixture with a peroxy initiator, heating to react for a certain time, cleaning a product, and drying to obtain the maleic anhydride grafted graphene material. According to the preparation method, graphene is grafted with strong polar groups to serve as a connecting bridge between the graphene and a plastic matrix, so that the strong bonding capacity between the graphene and the plastic matrix is obtained, then the toughness, surface smoothness, breaking strength and other mechanical properties of the corresponding plastic heat-conducting composite material are improved, and meanwhile the heat-conducting property of the heat-conducting composite material is remarkably improved. In addition, maleic anhydride and graphene are directly mixed without the help of an organic solvent or a dispersing agent and the like, the process is simple and pollution-free, the environmental protection property is improved, and the complexity of the preparation process is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of carbon materials, and in particular to a preparation method and application of a thermal conductive material and a maleic anhydride grafted graphene material. Background Art

[0002] In many fields such as electronics, aerospace and chemical industry, a large amount of thermal conductive materials are needed, such as heat sinks for electronic devices. Traditional thermal conductive devices are usually made of lightweight metals such as aluminum, but they are heavy and have high processing costs, which is not conducive to industrialization and precision applications. In order to reduce costs and improve production efficiency, related technologies use thermal conductive plastic composite materials to replace metal materials, such as using thermal conductive particles such as metal oxides, borides, graphite or graphene microsheets to compound with nylon. The resulting products are not only low in cost but also lighter in weight. Among them, the high thermal conductivity of graphene microsheets has the best application prospects. However, there are no polar groups on graphene microsheets, and the bonding ability with plastic matrices such as nylon is poor. There are many problems such as broken strips, rough surface and poor toughness during extrusion, low yield and short life. The toughness problem is particularly prominent. The reason is that the bonding between the matrix and the graphene microsheets is poor, causing cracks to develop along the bonding surface between the plastic matrix and the graphene microsheets during impact, which leads to very poor toughness of injection molded products. Summary of the invention

[0003] In view of the above problems in the prior art, the present application provides a preparation method and application of a thermal conductive material and a maleic anhydride grafted graphene material. The specific technical scheme is as follows:

[0004] On the one hand, the present application provides a method for preparing a maleic anhydride grafted graphene material, the preparation method comprising:

[0005] uniformly mixing maleic anhydride and graphene to obtain a preformed mixture;

[0006] The prefabricated mixture is mixed evenly with a peroxide initiator, heated to react for a certain period of time, and the product is washed and dried to obtain a maleic anhydride grafted graphene material.

[0007] In a possible implementation manner, the step of uniformly mixing maleic anhydride and graphene to obtain a prefabricated mixture comprises:

[0008] The maleic anhydride powder and the graphene powder are added into a mixer and stirred to obtain the prefabricated mixture.

[0009] In a possible embodiment, the mixer is preheated to 40-55° C. before adding maleic anhydride and graphene into the mixer.

[0010] In a possible implementation manner, the maleic anhydride powder and the graphene powder are stirred in the mixer for 15-30 minutes.

[0011] In a possible implementation manner, the stirring speed of the maleic anhydride powder and the graphene powder in the mixer is 5-50 rpm.

[0012] In a possible implementation manner, the step of uniformly mixing maleic anhydride and graphene to obtain a prefabricated mixture comprises:

[0013] providing an aqueous solution of maleic anhydride;

[0014] The graphene and the maleic anhydride aqueous solution are mixed and dried by a spray drying method to obtain the prefabricated mixture.

[0015] In a possible implementation manner, the graphene is physical method graphene or physical method graphene microplatelets, or a combination of physical method graphene and physical method graphene microplatelets, which is prepared by a physical exfoliation method.

[0016] In a possible implementation manner, the weight ratio between maleic anhydride and graphene added to form the prefabricated mixture is (2-5):50.

[0017] In a possible implementation manner, the grafting rate of the maleic anhydride grafted graphene material is 3-8%.

[0018] In a possible implementation manner, the weight ratio between the peroxy initiator and the graphene is (1-3):1000.

[0019] In a possible implementation manner, the reaction temperature between the prefabricated mixture and the peroxy initiator is 90-180° C., and the reaction time is 12-28 hours.

[0020] On the other hand, the present application provides an application of a maleic anhydride grafted graphene material prepared by the preparation method as described above in a thermal conductive material.

[0021] In another aspect, the present application provides a method for preparing a thermally conductive material, the method comprising:

[0022] Providing a maleic anhydride grafted graphene material prepared by the preparation method as described above;

[0023] The maleic anhydride grafted graphene material is mixed with a plastic matrix material and granulated to obtain a maleic anhydride grafted graphene / plastic composite material.

[0024] Based on the above technical solution, this application has the following beneficial effects:

[0025] The present application uses maleic anhydride and graphene to mix evenly to obtain a prefabricated mixture, and mixes it evenly with a peroxy initiator, and heats the reaction to obtain a maleic anhydride-grafted graphene material, so that the graphene is grafted with a strong polar group as a connecting bridge with the plastic matrix to obtain a strong bonding ability with the plastic matrix, thereby improving the mechanical properties such as toughness, surface smoothness and fracture strength of the corresponding plastic thermally conductive composite material, and significantly improving the thermal conductivity of the thermally conductive composite material. In addition, maleic anhydride and graphene are directly mixed without the aid of organic solvents or dispersants, etc., and the process is simple and pollution-free, which improves environmental protection and reduces the complexity of the preparation process. DETAILED DESCRIPTION

[0026] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0027] For the following defined terms, these definitions shall apply unless a different definition is given in the claims or elsewhere in this specification. All numerical values, whether explicitly indicated or not, are defined herein as modified by the term "about". The term "about" generally refers to a numerical range that a person of ordinary skill in the art considers to be equivalent to the stated values ​​to produce substantially the same properties, functions, results, etc. A numerical range indicated by a lower value and a higher value is defined to include all numerical values ​​included in the numerical range and all subranges included in the numerical range.

[0028] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions.

[0029] The following describes the preparation method of maleic anhydride grafted graphene material provided in the embodiment of the present application. This specification provides the method operation steps as in the embodiment, but may include more or fewer operation steps based on conventional or non-creative labor. The order of steps listed in the embodiment is only one way of executing the order of many steps and does not represent the only execution order. When the preparation method is actually executed, it can be executed in the order of the method shown in the embodiment or in parallel. The preparation method includes S1-S2:

[0030] S1: mixing maleic anhydride and graphene uniformly to obtain a prefabricated mixture;

[0031] S2: uniformly mixing the prefabricated mixture and the peroxide initiator, heating and reacting for a certain period of time, and washing and drying the product to obtain the maleic anhydride grafted graphene material.

[0032] Based on the above scheme, graphene is grafted with strong polar groups as a connecting bridge with the plastic matrix to obtain strong bonding ability with the plastic matrix, thereby improving the mechanical properties such as toughness, surface smoothness and fracture strength of the corresponding plastic thermally conductive composite material, and significantly improving the thermal conductivity of the thermally conductive composite material. In addition, maleic anhydride and graphene are directly mixed without the aid of organic solvents or dispersants, and the process is simple and pollution-free, which improves environmental protection and reduces the complexity of the preparation process.

[0033] In some embodiments, the graphene is physical method graphene or physical method graphene microsheets, or a combination of physical method graphene and physical method graphene microsheets, which is prepared by a physical exfoliation method.

[0034] In a possible embodiment, graphene is prepared by adding graphite to water to form a suspension, and then exfoliating by ultrasound or shearing, and exfoliating the graphite into graphene by a physical method. By adopting a physical method, a graphene material with high purity, high crystallinity, excellent thermal conductivity and processing performance is obtained, the graphene structure is complete and has few defects, and the performance of maleic anhydride grafted graphene is improved, so that the thermal conductive material obtained by adding it has excellent mechanical properties and thermal conductivity, and the preparation of graphene microsheets is environmentally friendly and pollution-free. In a possible embodiment, the thickness of physical method graphene can be less than 10 layers of carbon atoms, and the thickness of physical method graphene microsheets is more than 10 layers of carbon atoms, which can be specifically 5-100nm, preferably 30-90nm.

[0035] In a preferred embodiment, the graphene is physically produced graphene microsheets, which can be added in an increased amount at a low cost, thereby improving product performance while reducing the impact on material fluidity and mechanical properties.

[0036] In a possible implementation manner, the diameter of the graphene sheet used is 10-200 μm, preferably 50-150 μm.

[0037] In some embodiments, the weight ratio of maleic anhydride and graphene added to form the prefabricated mixture is (2-5):50, and can be any point value within the above range such as 2:50, 3:50, 4:50, 5:50, etc., which are not enumerated here. The above ratio can make the grafting rate of maleic anhydride grafted graphene material meet the application requirements, can be strongly connected with base materials such as plastics, and avoid excessive maleic anhydride causing excessive by-products.

[0038] Based on some or all of the above embodiments, in some embodiments, S1 may include S11: adding maleic anhydride powder and graphene powder into a mixer and stirring and mixing to obtain the prefabricated mixture. In this way, maleic anhydride is evenly coated on the graphene surface by directly using the powder mixing method, and then the peroxide initiator is added and mixed evenly, so that the initiator can also be evenly dispersed and fully contacted with maleic anhydride and graphene, effectively improving the efficiency and uniformity of the subsequent grafting reaction, so that maleic anhydride is added and grafted onto the graphene surface, without the need for organic solvents and other solvent components, and the process is simple and pollution-free.

[0039] In some embodiments, before adding maleic anhydride and graphene to the mixer, the mixer is preheated to 40-55°C, preferably 50°C, so that the maleic anhydride can be easily stirred by preheating to melt and apply to the surface of the graphene, thereby avoiding maleic anhydride sticking to the wall and uneven coating. The temperature is preferably slightly lower than the melting point, which is conducive to the addition of maleic anhydride and the heat generated by subsequent stirring to quickly reach the melting point.

[0040] In some embodiments, the stirring time of maleic anhydride powder and graphene powder in the mixer is 15-30 minutes; the stirring speed of maleic anhydride powder and graphene powder in the mixer is 5-50 rpm, preferably 20-40 rpm. In this way, the uniform coating and sufficient contact of maleic anhydride on the graphene surface are ensured, which is beneficial to the subsequent addition grafting reaction.

[0041] In some other embodiments, S1 may include S21: providing an aqueous solution of maleic anhydride; mixing and drying the graphene with the aqueous solution of maleic anhydride by spray drying to obtain the prefabricated mixture. In this way, the aqueous solution of maleic anhydride and the graphene are fully mixed by spray drying, which reduces dust pollution in the preparation process and ensures the environmental protection of the raw materials, while improving the mixing uniformity and the maleic anhydride coating effect on the graphene surface. Specifically, a spray drying device can be used to mix and dry the graphene powder with the maleic anhydride solution to obtain a graphene mixture uniformly coated with maleic anhydride.

[0042] In some embodiments, the weight ratio of the peroxy initiator to the graphene is (1-3):1000, and specifically can be any point value within the above range such as 1:1000, 2:1000, 3:1000, etc., which are not enumerated here. The graphene is fully grafted by adding the peroxy initiator, and the peroxy initiator can include but is not limited to tert-butyl peroxy-2-ethylhexanoate (TBPO) and the like. In addition, the amount of the initiator added is controlled to the above range to achieve sufficient grafting while avoiding excessive initiator.

[0043] In some embodiments, the peroxygen initiator is a liquid.

[0044] In some embodiments, in S2, the cooled prefabricated mixture is mixed with the peroxy initiator at room temperature by high-speed stirring, the stirring temperature is room temperature, and the stirring time is 5-10 minutes, so as to achieve full dispersion and coating of the peroxy initiator before the grafting reaction.

[0045] In some embodiments, the reaction temperature between the prefabricated mixture and the peroxy initiator is 90-180°C, and the reaction time is 12-28h. Preferably, the reaction temperature is 100°C; preferably, the reaction time is 24h. By controlling the reaction temperature and time, the efficiency and completeness of the grafting reaction are improved. Specifically, after the reaction is completed, the product is rinsed with water, filtered and dried to remove unreacted maleic anhydride and the reaction by-product polymaleic anhydride, and pure maleic anhydride grafted graphene is obtained.

[0046] In some embodiments, the grafting rate of the prepared maleic anhydride grafted graphene material is 3-8%.

[0047] The present application also provides an application of the maleic anhydride grafted graphene material prepared by the above preparation method in a thermal conductive material. The maleic anhydride grafted graphene material is used as an additive and mixed with a plastic matrix material to form a composite thermal conductive material of the plastic material and the grafted graphene, which has excellent mechanical properties and thermal conductivity.

[0048] The present application also provides a method for preparing the above-mentioned thermal conductive material, which specifically comprises: providing a maleic anhydride grafted graphene material prepared by the above-mentioned preparation method; mixing and granulating the maleic anhydride grafted graphene material with a plastic matrix material to obtain a maleic anhydride grafted graphene / plastic composite material.

[0049] The plastic matrix material may be a resin material, including but not limited to nylon 6, etc. The plastic matrix and the maleic anhydride grafted graphene material may be mixed in a high-speed mixer, and added to a twin-screw extruder for mixing and granulation.

[0050] In some embodiments, the temperature of the extruder is set to 250-270° C., and the screw speed is 100-300 rpm.

[0051] In some embodiments, the mass ratio between the maleic anhydride grafted graphene material and the plastic matrix material is 10:90 to 80:20, preferably 40:60 to 50:50.

[0052] This application uses maleic anhydride grafted graphene material as an additive material to ensure that graphene and plastic matrix materials are bridged by means of maleic anhydride groups, which greatly improves the combination of physical graphene and matrix resin / solvent. There is no need to add maleic anhydride during the extrusion granulation process, which solves the problem of poor toughness of high thermal conductivity plastic composite materials, and obtains composite thermal conductive materials with excellent mechanical properties and thermal conductivity and smooth surface. The preparation cost is low and the process is environmentally friendly. The thermal conductivity of the prepared thermal conductive material can reach more than 5W / (m·K). It should be noted that the above thermal conductivity value is measured perpendicular to the product plane. Using a measurement method parallel to the surface, the thermal conductivity of the obtained material can reach more than 50W / (m·K).

[0053] The following describes specific embodiments of the present application in combination with the above-mentioned thermal conductive material, preparation method and application of maleic anhydride grafted graphene material.

[0054] The preparation method of the maleic anhydride grafted graphene material and the thermal conductive material in Examples 1-5 comprises the following steps:

[0055] Preparation of maleic anhydride grafted graphene material:

[0056] (1) Heat a high-speed mixer to 50°C, add maleic anhydride with a weight of M1 and physical graphene microsheets with a weight of M2, stir at high speed for 20 minutes, take out, and obtain a prefabricated mixture; or, dissolve maleic anhydride with a weight of M1 in water to obtain a maleic anhydride aqueous solution. Mix and dry the physical graphene microsheets with a weight of M2 and the maleic anhydride aqueous solution in a spray drying device, take out, and obtain a prefabricated mixture;

[0057] (2) After the prefabricated mixture obtained in step (1) is cooled, it is poured into another high-speed mixer at room temperature, and then TBPO with a weight of M3 is added and stirred at high speed for 5 minutes;

[0058] (3) placing the material obtained in step (2) into an oven and reacting at a temperature of 90-180° C. for 24 hours, and washing the product with water, filtering and drying to obtain a maleic anhydride grafted graphene material.

[0059] The reaction scheme of the above embodiment is as follows:

[0060]

[0061] Preparation of thermal conductive material: The maleic anhydride grafted graphene material obtained in step (3) and nylon 6 are mixed in a high-speed mixer, and then added into a twin-screw extruder for mixing and granulation. The temperature of the extruder is set to 250-270° C. and the screw speed is 100-300 rpm to obtain a thermal conductive material composite of nylon and maleic anhydride grafted graphene.

[0062] In Comparative Examples 1 and 2, the physical method graphene microsheets were mixed with nylon 6 using a high-speed mixer, and the thermally conductive composite material was obtained using the thermally conductive material preparation method in the embodiment. In Comparative Example 2, a toughening agent POE-g-MAH was added during the mixing and granulation process, and the mass ratio of PA6 to the toughening agent was M4:M6.

[0063] Comparative Examples 3 and 4 adopt the method of the embodiment to prepare maleic anhydride grafted graphene material and thermal conductive material, the difference is that the proportion of raw materials in the preparation process of maleic anhydride grafted graphene material is different.

[0064] In Comparative Example 5, the prefabricated mixture obtained in step (1) of Example (equivalent to graphene surface-modified with maleic anhydride) was mixed with nylon 6 for granulation, and other parameters were the same as those in Example to obtain a thermally conductive material.

[0065] Among them, the mass ratio of nylon 6 to maleic anhydride grafted graphene material, the mass ratio of nylon 6 to physical graphene microsheets, or the mass ratio of nylon 6 to maleic anhydride surface modified graphene is M4:M5.

[0066] The reaction parameters of the above embodiments and comparative examples are shown in Table 1 below, and the relevant performance test results of the thermal conductive material are shown in Table 2.

[0067] Table 1

[0068]

[0069]

[0070] Table 2

[0071]

[0072]

[0073] Based on the above table 1 and table 2, it can be known that high-content graphene-filled nylon thermoplastic materials generally have poor mechanical properties, especially poor toughness (impact strength). Simply adding a toughening agent, no matter how the type and content of the toughening agent are adjusted, can not improve toughness. The reason is that graphene-based materials are inert materials, and the bonding force between them and plastics is very poor, causing cracks to develop along the bonding surface of the plastic matrix and graphene during impact. Maleic anhydride is grafted onto the graphene surface, and the bonding force of plastic and graphene can be greatly improved. From a macroscopic point of view, the mechanical properties of the material are improved. At the same time, the improvement of the bonding force makes graphene disperse better, and also improves the thermal conductivity of the material. Simply applying maleic anhydride to the surface of graphene cannot have an effect. The material prepared by the method of the present application can make maleic anhydride well grafted to the graphene surface, the grafting rate can reach more than 3%, the performance of the thermal conductive material can be improved, the tensile strength can reach more than 50Mpa, the elongation at break can reach more than 1%, the bending strength can reach more than 78Mpa, the bending modulus can reach more than 10000Mpa, the notched impact strength can reach more than 3.6KJ / m2, and the thermal conductivity can reach more than 5.9W / m·K.

[0074] The above description has fully disclosed the specific implementation methods of the present application. It should be pointed out that any changes made by technicians familiar with the field to the specific implementation methods of the present application do not deviate from the scope of the claims of the present application. Accordingly, the scope of the claims of the present application is not limited to the above specific implementation methods.

Claims

1. A method for preparing a maleic anhydride grafted graphene material, characterized in that: The preparation method comprises: uniformly mixing maleic anhydride and graphene to obtain a preformed mixture; The prefabricated mixture is mixed evenly with a peroxide initiator, heated to react for a certain period of time, and the product is washed and dried to obtain a maleic anhydride grafted graphene material.

2. The preparation method according to claim 1, characterized in that: The step of uniformly mixing maleic anhydride and graphene to obtain a prefabricated mixture comprises: The maleic anhydride powder and the graphene powder are added into a mixer and stirred to obtain the prefabricated mixture.

3. The preparation method according to claim 2, characterized in that: Before adding maleic anhydride and graphene into the mixer, preheat the mixer to 40-55° C.; The stirring time of the maleic anhydride powder and the graphene powder in the mixer is 15-30 minutes; The stirring speed of the maleic anhydride powder and the graphene powder in the mixer is 5-50 rpm.

4. The preparation method according to claim 1, characterized in that: The step of uniformly mixing maleic anhydride and graphene to obtain a prefabricated mixture comprises: providing an aqueous solution of maleic anhydride; The graphene and the maleic anhydride aqueous solution are mixed and dried by a spray drying method to obtain the prefabricated mixture.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The graphene is physical method graphene or physical method graphene microsheet, or a combination of physical method graphene and physical method graphene microsheet, and is prepared by a physical exfoliation method.

6. The preparation method according to any one of claims 1 to 4, characterized in that: The weight ratio of maleic anhydride and graphene added to form the prefabricated mixture is (2-5):50; The grafting rate of the maleic anhydride grafted graphene material is 3-8%.

7. The preparation method according to any one of claims 1 to 4, characterized in that: The weight ratio between the peroxy initiator and the graphene is (1-3):1000.

8. The preparation method according to any one of claims 1 to 4, characterized in that: The reaction temperature between the prefabricated mixture and the peroxy initiator is 90-180° C., and the reaction time is 12-28 hours.

9. Use of the maleic anhydride grafted graphene material obtained by the preparation method according to any one of claims 1 to 8 in thermal conductive materials.

10. A method for preparing a thermally conductive material, characterized in that: The preparation method comprises: Providing a maleic anhydride grafted graphene material prepared by the preparation method according to any one of claims 1 to 8; The maleic anhydride grafted graphene material is mixed with a plastic matrix material and granulated to obtain a maleic anhydride grafted graphene / plastic composite material.

Citation Information

Cited By

  • High-barrier polypropylene packaging film and preparation method thereof

    CN121424786A

  • Heating temperature-regulating fiber and preparation method thereof

    CN121538760A